TI_GERICHTE 35.2005.20 vom 13. Juni 2005 , stralcio della causa dai ruoli per intervenuta transazione, omologata dal TCA - TI Tribunale d'appello (2005)
stralcio della causa dai ruoli per intervenuta transazione, omologata dal TCA